PROJECT OF A REHABILITATION CENTRE FOR MILITARY PERSONNEL AND WAR VETERANS IN ZHYTOMYR, WHICH WON FIRST PLACE IN THE «STEEL FREEDOM» ARCHITECTURAL COMPETITION (Collection of scientific works «Modern structures of metal and wood», 2024)
The article is devoted to the study of the experience of using metal structures in the design of rehabilitation centres on the example of the project of the R-240 team ‘Rehabilitation Centre for Military Personnel and War Veterans in Zhytomyr’ for the Steel Freedom competition. Due to the Russian invasion of Ukraine, a large number of military personnel have suffered physical and mental injuries. As a result, the need for rehabilitation centres has increased. The engineering and architectural community is faced with the challenge of finding ways to meet these demands. Metal structures,  due  to  their  high  reliability,  industrial  nature,  the  ability  to  provide  architectural expression, the isotropic nature of the material itself and their invulnerability to various factors, are best  suited  for  this  purpose.  When  working  on  the  project  of  a  rehabilitation  centre  for  military personnel and war veterans in Zhytomyr, a metal frame was used, and relevant calculations were carried out to prove its effectiveness. The structural scheme of the projected rehabilitation centre is a metal frame and ligature frame, in which columns and crossbars form the main flat supporting units of the frame system - transverse frames. As the building is quite large in plan (91.5×68.9 m in axes), has different heights of individual parts and is multifunctional, there is a possibility of significant deformation of the frame elements due to daily and annual temperature fluctuations and different temperature and humidity conditions of the premises. To avoid uncontrolled adverse movements and to differentiate between zones with different purposes, the building is divided into three blocks by expansion joints. Each block is an independent frame that is not connected to adjacent structures. A distinctive feature of the frame is the spatial cantilever structure with a 9 m overhang. The high ratio between  the  strength  and  density  of  steel  and  the  permissible  deflection  values  obtained  in  the calculation programme prove the feasibility of using steel structures and the reality of the plan. The study proves that the use of a metal frame is best suited for the construction of new buildings and structures, as well as the reconstruction of existing facilities during the post-war reconstruction of Ukraine.